2000
DOI: 10.1007/s007020070022
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological effects of milnacipran, a new antidepressant, given repeatedly on the α 1 -adrenergic and serotonergic 5-HT 2A systems

Abstract: Milanacipran (MIL) is a representative of a new class of antidepressants (SNRIs) which inhibit selectively the reuptake of serotonin and noradrenaline but, in contrast to tricyclics, show no affinity for neurotransmitter receptors. The present study was aimed at determining whether repeated MIL treatment induced adaptive changes in the alpha1-adrenergic and serotonergic 5-HT2A systems, similar to those reported by us earlier for tricyclic antidepressants. The experiments were carried out on male mice and rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Another possible explanation is that an indirect pathway, such as a changing affinity for an agonist, may be involved in the effect of milnacipran, rather than direct effects on the α 1 -adrenoceptor. In support of this hypothesis, there is a report suggesting that milnacipran enhances the ability of α 1 -adrenoceptor agonists to compete for the [ 3 H]prazosin binding site without changing the number of binding sites or the affinity for [ 3 H]prazosin in the rat brain cortex (Maj et al, 2000). However, further studies into this issue will be needed.…”
Section: Discussionmentioning
confidence: 84%
“…Another possible explanation is that an indirect pathway, such as a changing affinity for an agonist, may be involved in the effect of milnacipran, rather than direct effects on the α 1 -adrenoceptor. In support of this hypothesis, there is a report suggesting that milnacipran enhances the ability of α 1 -adrenoceptor agonists to compete for the [ 3 H]prazosin binding site without changing the number of binding sites or the affinity for [ 3 H]prazosin in the rat brain cortex (Maj et al, 2000). However, further studies into this issue will be needed.…”
Section: Discussionmentioning
confidence: 84%
“…Many authors have reported that chronic treatment with tricyclic antidepressants or ECS increases either the density (Maj et al, 1985;Nowak et al, 1988;Vetulani et al, 1984), agonist affinity (Maj et al, 2000;Menkes et al, 1983a), electrophysiological response (Menkes et al, 1980), or behavioral response of brain a 1 -receptors (Maj et al, 1998(Maj et al, , 2000Menkes et al, 1983b;Mogilnicka et al, 1987;Plaznik et al, 1984). As noted above, an antidepressant, citalopram, was also shown to reverse the stressinduced desensitization of the a 1 -potentiation of cAMP responses.…”
Section: Effects Of Stress and Depression On Epi-a 1 -Systemmentioning
confidence: 94%
“…SNRIs) decrease the DOI-elicited HTR. [122,123] Similarly, repeated exposure to MDMA, which acts partially through interactions with the serotonin, dopamine, and norepinephrine transporters, may alter sensitivity to DOI. Although one early paper suggested no lasting effect of MDMA administration, [124] a more recent report found that repeated MDMA treatment resulted in an enhanced sensitivity to DOI at a higher (3.0 mg/kg) but not a lower dose (0.5 mg/kg).…”
Section: Receptor Systems Involved In the Htr Induced By Doimentioning
confidence: 99%